Factors affecting student concept formation towards planned action in environmental education - Sombilon, Sheryl J. (2014)
This study aimed to investigate the factors affecting concept formation leading to planned action in environmental education and the hierarchy of factors as perceived by the research participants. The data were gathered primarily through the use of concept maps, interview questions and task sheets. The common factors affecting concept formation that led to planned actions among the research participants were previous experiences, exposure to various teaching methods, attendance and participation to lecture or forums, television, radio, online resources, books and periodicals, campaign material, film and book reviews. The factors identified in the study that led to concept development enabled the participants to formulate suitable set of action plans to EE topics they were exposed to during the data collection period. The hierarchy of factors that influenced concept formation and action planning exhibited variation among the members of the focus group.
Keywords: Environmental education; Environmental literacy